THE EXTRACT IS HIGHLY EFFECTIVE IN ARTERIAL HYPERTENSION ATHEROSCLEROSIS AND NEUROSES ITS ROOT IS TREATMENT FOR RHEUMATOLOGY GOUT AND DENTAL DISEASES THE ASPARAGUS IS AN INNOVATIVE VALUE IN MEDICINE AND MODERN PHARMACEUTICALS - Akbarov Asliddin; Matkarimova Gulnaz (Galaxy International Interdisciplinary Research Journal, 2023)
Sarsabil has been widely used in medicine in the Mediterranean region since ancient times. It grows in Samarkand, Bukhara, Fergana and Tashkent regions of Uzbekistan. As a result of pharmacological and toxicological studies, phytopreparations of plant products have been found to have a wide range of therapeutic properties in the treatment of tachycardia and heart diseases, which boosts the immunity of liverwort. Cardiovascular diseases are the most common diseases, some of them are widespread on the earth and the complications are fatal or seriously affecting health, ischemic heart disease (IHD), heart attack (rheumocarditis), and other diseases. causes heart failure. Atherosclerosis in this disease occurs as a result of the breakdown of fat metabolism in the inner intima layer of the arterial blood vessel wall, and as a result, the elasticity (elasticity) of the blood vessel wall is broken, it hardens, and the space narrows. If the tissue blood supply worsens, such a change occurs in the blood vessels of the brain, heart, and kidneys, life-threatening diseases (insulinism, angina pectoris, myocardial infarction, etc.) occur. The root and extract of the medicinal plant sarsabil, which grows naturally in Samarkand, is highly effective for the above-mentioned diseases and the diseases mentioned in the subject of the scientific article.